2020
DOI: 10.1042/bsr20200986
|View full text |Cite
|
Sign up to set email alerts
|

Pinocembrin alleviates ulcerative colitis in mice via regulating gut microbiota, suppressing TLR4/MD2/NF-κB pathway and promoting intestinal barrier

Abstract: Pinocembrin, a plant-derived flavonoid, has a variety of pharmacological activities, including anti-infection, anti-cancer, anti-inflammation, cardiovascular protection, etc. However, the mechanism of pinocembrin on the anti-colitis efficacy remains elusive and needs further investigation. Here, we reported that pinocembrin eased the severity of dextran sulfate sodium (DSS)-induced colitis in mice by suppressing the abnormal activation of toll-like receptor 4 (TLR4) / nuclear factor-kappa B (NF-κB) signal path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Moreover, significant alterations were observed in DSS-treated mice, as levels of Firmicutes were reduced at the phylum level and those of Escherichia-Shigella were increased at the genus level; however, acacetin alleviated these changes. Notably, this results are quite consistent with our previously studied natural compounds, including obacunone and pinocembrin ( Luo et al, 2020 ; Yue et al, 2020 ). There are also some researches indicate that Escherichia-Shigella are positively correlated with high expression of inflammatory cytokines, and many studies have shown its adverse effects in IBD ( Zeissig et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, significant alterations were observed in DSS-treated mice, as levels of Firmicutes were reduced at the phylum level and those of Escherichia-Shigella were increased at the genus level; however, acacetin alleviated these changes. Notably, this results are quite consistent with our previously studied natural compounds, including obacunone and pinocembrin ( Luo et al, 2020 ; Yue et al, 2020 ). There are also some researches indicate that Escherichia-Shigella are positively correlated with high expression of inflammatory cytokines, and many studies have shown its adverse effects in IBD ( Zeissig et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…TLR4, one of the best characterized pattern recognition receptors, is activated by LPS, leading to the activation of NF-κB and subsequently inducing the production of proinflammatory mediators. Recently, many studies have indicated that NF-κB is a key factor in inflammatory gene expression [37][38][39]. Under normal conditions, NF-κB binds with IκB to form an inactivation complex.…”
Section: Discussionmentioning
confidence: 99%
“…It has been investigated that diplacone and mimulone protect rats from DSS-induced colitis through increments in antioxidant activity and modulation of metalloproteinase activity [ 20 ]. A recent report has evaluated the protective effect of pinocembrin on colitis, whereby it suppresses gut microbiota and toll like receptor 4/myeloid differentiation factor 2/NF-κB pathway but enhances the intestinal barrier by upregulating the expression of tight junction proteins [ 21 ]. Since the literature reports on the potent bioactivities of flavanone family on the attenuation of colitis, further studies should look at whether THF has an antioxidant activity, modulates metalloproteinase activity or increases intestinal barrier function in colonic inflammation conditions.…”
Section: Discussionmentioning
confidence: 99%